Estandarización de los procesos productivos para mejorar la eficiencia en la empresa “CAPOLIVERY” - Sánchez Rosero, José Israel (2021)
This research project was carried out in the textile company "Capolivery" located in the city of Ambato, dedicated to the manufacture of clothing for women, men, the development is based on the standardization of production processes to improve efficiency in the company, According to the need that is presented in the company, the recognition and the route of the process that is handled was made, identifying each stage and the causes and consequences that are immersed affecting the productive system, applying the inductive and explanatory methods for which a Layout of the process of making polo shirts was made as the main tool of knowledge. Once the above was identified for the standardization, several samples of polo shirts were taken, using the method of time study in the company, the time of each process of making each shirt was taken, all this information was reflected in the process diagram with the respective times and the precedence diagram, performing the calculations, the cycle time of each sample of men and women was obtained, then proceeded to calculate by the formulas of the method of study the units produced per hour, day, and week to know the cycle time of each sample of men and women, As a result, a method was proposed to improve the efficiency of the process followed by a comparison of the current method with the proposed method and a percentage increase in production was obtained by this virtue and consequently the efficiency of the production system was improved.